2018
DOI: 10.1111/cas.13516
|View full text |Cite
|
Sign up to set email alerts
|

RBBP6 increases radioresistance and serves as a therapeutic target for preoperative radiotherapy in colorectal cancer

Abstract: Radiotherapy (RT) can be used as preoperative treatment to downstage initially unresectable locally rectal carcinoma, but radioresistance and recurrence remain significant problems. Retinoblastoma binding protein 6 (RBBP6) has been implicated in the regulation of cell cycle, apoptosis and chemoresistance both in vitro and in vivo. The present study investigated whether the inhibition of RBBP6 expression would improve radiosensitivity in human colorectal cancer cells. After SW620 and HT29 cells were exposed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 36 publications
4
22
0
Order By: Relevance
“…It is known that RBBP6 is closely involved in the bioprocesses of many different cancers (Dlamini, Mbita, Rupnarain, Ledwaba, & Motadi, 2005). In present study, RBBP6 expressions in PCa tissues and PCa cell lines (LNCap, PC3, and DU145) were higher than that in the noncancerous BPH tissues and the normal human prostate epithelial cell line RWPE‐1, respectively, which was consistency with previous studies in colon cancer (Dlamini et al, 2016), colorectal cancer (Xiao et al, 2018), hepatocellular carcinoma (Mbita & Dlamini, 2006), and so on. Furthermore, overexpressed RBBP6 in tumorous tissues was also associated with clinical stage, depth of tumor invasion, lymph node metastasis, distant metastasis, and histologic grade, and it was also closely related to a poor prognosis of patients with gastric cancer, cervical carcinoma, and colon cancer, indicating its role as an independent prognostic factor (Chen et al 2013; Morisaki et al 2014; Teng et al 2018).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It is known that RBBP6 is closely involved in the bioprocesses of many different cancers (Dlamini, Mbita, Rupnarain, Ledwaba, & Motadi, 2005). In present study, RBBP6 expressions in PCa tissues and PCa cell lines (LNCap, PC3, and DU145) were higher than that in the noncancerous BPH tissues and the normal human prostate epithelial cell line RWPE‐1, respectively, which was consistency with previous studies in colon cancer (Dlamini et al, 2016), colorectal cancer (Xiao et al, 2018), hepatocellular carcinoma (Mbita & Dlamini, 2006), and so on. Furthermore, overexpressed RBBP6 in tumorous tissues was also associated with clinical stage, depth of tumor invasion, lymph node metastasis, distant metastasis, and histologic grade, and it was also closely related to a poor prognosis of patients with gastric cancer, cervical carcinoma, and colon cancer, indicating its role as an independent prognostic factor (Chen et al 2013; Morisaki et al 2014; Teng et al 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Silencing RBBP6 was reported to effectively prevent breast cancer cells from stable growth and proliferation (Moela et al, 2014). A recent study confirmed that RBBP6 overexpression endows colorectal cancer cells with antiapoptotic effects (Xiao et al, 2018), which is also indicated to be a potential marker of cervical cancer cell apoptosis and cell cycle arrest (Moela & Motadi, 2016). Xiao et al (2018) found transfection with RBBP6 short hairpin RNA improved the levels of G2‐M phase arrest, which blocked the cells in a more radiosensitive period of the cell cycle.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The xenograft tumors were fixed in 10% formalin, dehydrated in a graded series of alcohol, and embedded in paraffin. Four micrometer thick slices were stained with hematoxylin and eosin, and immunohistochemistry (IHC) was subsequently performed as previously described (21). Briefly, the slices were incubated with the primary antibody against PHLDA2 (Abcam, USA), Ki67 and cleaved caspase-3 (Santa Cruz biotechnology, CA) at 4°C overnight, and subsequently stained with a biotinylated secondary antibody (Zhongshan, China) at room temperature for 1 h. Negative controls without a primary antibody were processed in parallel.…”
Section: Methodsmentioning
confidence: 99%
“…However, human cancers are increasingly recognized as a heterogeneous disease, and not all patients derive a survival benefit from radiotherapy. Radiation resistance can easily lead to incomplete cure, recurrence, and metastasis [ 2 ]. Therefore, understanding the mechanism contributing to radioresistance is pivotal to exploring strategies to improve cancer radiotherapy.…”
Section: Introductionmentioning
confidence: 99%